Estimating the Costs of Partial-Coverage Rent Controls: A Stochastic Frontier Approach - Caudill, Steven B. (The Review of Economics and Statistics, 1993)
This paper presents a modified frontier approach to estimate hedonic regressions for data on rent-controlled and uncontrolled apartments. This new approach allows the author to estimate the size of the subsidy from landlords to tenants of rent-controlled apartments. In addition, this method provides the first estimates of the amount by which controls increase rents for uncontrolled apartments. The study shows that, in New York City in 1968, rents in the controlled sector would rise 22 to 26 percent upon decontrol, while rents in the uncontrolled sector would fall about 22 to 25 percent upon removal of rent controls. Copyright 1993 by MIT Press.